2007
DOI: 10.1007/s10924-007-0055-6
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable nanocomposites based on poly(butylene succinate)/organoclay

Abstract: In this work, we try to incorporate the inorganic system into the biodegradable polymers to compose an organic/inorganic polymer hybrid. Various nanocomposites of poly(butylene succinates) (PBS) with different ratios of organically modified layered silicates (OMLS) prepared by solution blending were investigated. The OMLS used for the preparation of nanocomposites were functionalized ammonium salts modified montmorillonite. The effects of OMLS on the nanocomposites were investigated by XRD, TEM, DMA and TGA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 34 publications
7
59
0
Order By: Relevance
“…With the purpose of improving the performance and reducing the cost of PBS-based materials, cellulose acetate, 11 soy protein, 12 corn starch, 13,14 chitosan, 15 layered silicate, 3,16 organoclay, 17 attapulgite, 18 carbon nanotubes, 19 poly(lactic acid), 20 and poly (ethylene oxide) 21 have been introduced to modify the PBS plastics.…”
Section: Introductionmentioning
confidence: 99%
“…With the purpose of improving the performance and reducing the cost of PBS-based materials, cellulose acetate, 11 soy protein, 12 corn starch, 13,14 chitosan, 15 layered silicate, 3,16 organoclay, 17 attapulgite, 18 carbon nanotubes, 19 poly(lactic acid), 20 and poly (ethylene oxide) 21 have been introduced to modify the PBS plastics.…”
Section: Introductionmentioning
confidence: 99%
“…It can be processed in the field of textiles into melt-blown, multifilament, monofilament, flat and split yarn [1]. However, other properties such as gas barrier properties, melt viscosity for further processing and so on, are frequently insufficient for various end-use applica-tions [2]. Poly(butylene adipate-co-terephthalate) PBAT, trade name ECOFLEX ® is an aliphatic/aromatic copolyester based on the monomers 1,4-butanediol, adipic acid and terephthalic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of microcomposites has been reported by Someya et al (2004) when processing PBS and MMT-Na+ by melt intercalation. On the other hand, many researchers have reported obtaining well-intercalated structures when processing PBS with organo-modified clays such as C10A, C30B, MMT-LEA by either solvent casting, melt intercalation, or in situ polymerization Someya et al 2004;Shih et al 2007Shih et al , 2008Hwang et al 2009). Some authors have also reported the preparation of completely exfoliated PBS/clay nanocomposites by solvent casting (Shih et al 2007(Shih et al , 2008, melt intercalation , and in situ polymerization (Rong et al 2002) as well.…”
Section: Processing Of Biodegradable Clay Nanocompositesmentioning
confidence: 99%